A companion to translation studies / [electronic resource] - Bermann, Sandra, 1947-; Porter, Catherine, 1941- (Hoboken, New Jersey : Wiley-Blackwell, 2014)
"Multi-disciplinary relevance for students with diverse career goals"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Translating and interpreting -- Study and teaching (Higher); Translating and interpreting -- Vocational guidance; LITERARY CRITICISM / General; Translating and interpreting -- Study and teaching (Higher); Translating and interpreting -- Vocational guidance; Electronic books